1996
DOI: 10.1115/1.2823355
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cyclic Ratchetting Plasticity, Part I: Development of Constitutive Relations

Abstract: The existing plasticity models recognize that ratchetting direction strongly depends on the loading path, the stress amplitude, and the mean stresses, but their predictions deviate from experiments for a number of materials. We propose an Armstrong-Frederick type hardening rule utilizing the concept of a limiting surface for the backstresses. The model predicts long-term ratchetting rate decay as well as constant ratchetting rate for both proportional and nonproportional loadings. To represent the transient be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
177
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 387 publications
(203 citation statements)
references
References 31 publications
2
177
0
Order By: Relevance
“…3 (a) Incidentally, Jiang et al [35,36] showed that the material constants ƒÄi and ƒÁi in Eqs. (8), (10) and (11) can be determined systematically using the following equations if rate-independent plasticity with no isotropic hardening is assumed:…”
Section: Modificationsmentioning
confidence: 99%
“…3 (a) Incidentally, Jiang et al [35,36] showed that the material constants ƒÄi and ƒÁi in Eqs. (8), (10) and (11) can be determined systematically using the following equations if rate-independent plasticity with no isotropic hardening is assumed:…”
Section: Modificationsmentioning
confidence: 99%
“…For correct description of ratcheting in proportional and non-proportional loading more and more authors introduced a nonproportional parameter, which enables simultaneous correct description of uniaxial and multiaxial ratcheting (Chen & Jiao 2004;Chen, 2005;Halama, 2008). Significant improvements of prediction capability can be reached by using memory surfaces Sehitoglu, 1996 andDöring, 2003). Presented models should be compared in terms of nonlinearity, established for each backstress in the case of uniaxial loading.…”
Section: Other Cyclic Plasticity Modelsmentioning
confidence: 99%
“…The hysteresis loading curve (σ -ε p ) is divided into 12 segments. The corresponding kinematic hardening parameters (C (1) to C (12) and γ (1) to γ (12) ) are determined by the following equations as described by Bari and Hassan (2000) and Jiang and Sehitoglu (1996).…”
Section: Ohno-wang Model Parameters (I = 1 To 12)mentioning
confidence: 99%
“…Many advanced constitutive models have been developed to simulate the cyclic and time independent behaviours of the material. Armstrong and Frederick (1966), Abdel Ohno (2000a, 2000b), Bari and Hassan (2000, Chaboche (1986a), Chaboche et al (1979), Chaboche andRousselier (1986b, 1986c), Ohno and Wang (1991, 1993, 1994, Ohno (1998), Yoshida (2000), Yoshida and Uemori (2002), Ellyin and Xia (1989), Trampczynski and Mroz (1992), Haupt and Kamlah (1995), Jiang and Sehitoglu (1996), Kobayashi and Ohno (2002), Khutia et al (2013) and many others developed improved constitutive models for representing cyclic non-linear responses including ratcheting.…”
Section: Introductionmentioning
confidence: 99%